STIGMATIZATION OF PSYCHOSOCIAL MENTAL DISABILITIES THROUGH THE MENTION OF PEOPLE WITH MENTAL DISORDERS - Isrofillah, Fira (HEARTY, 2024)
Stigma against persons with psychosocial disabilities in the mass media causes people to be afraid to seek help and open up in public spaces. Stigmanisai in the mass media occurs through the designation ODGJ or People with Mental Disorders which should since the Law on Persons with Disabilities be referred to as persons with psychosocial mental disabilities. The study used the CADS method or Corpus Assisted Discourse Studies with the keywords mention of OGDJ and the relationship between word frequencies that appeared in the mass media whose results showed that the word ODGJ was dominated by news related to law enforcement through the institution of police power at various levels as bourgeois actions in the public sphere. The news also shows more about actions that in theory stigma as behavior that is strongly disapproved of by the social normal that is full of normal. This is a form of mass media framing of psychosocial mental people by serving the value of society as an interesting news article for readers and viewers to enjoy rather than advocating for people and disability issues as social justice issues that require broad access to appropriate treatment.